Root pruning improves maize water-use efficiency by root water absorption - Yan, Minfei; Zhang, Cong; Li, Hongbing; Zhang, Li; Ren, Yuanyuan; Chen, Yinglong; Cai, Huanjie; Zhang, Suiqi (Frontiers in Plant Science, 2023)
Root systems are important component of plants having significant impact on crop water-use efficiency (WUE) and yield. This study examined the effects of root pruning on maize yield, WUE, and water uptake under pot and hydroponic conditions. The pot experiment showed that root pruning significantly decreased root/shoot ratio. Both small root pruning (cut off about 1/5 of the root system, RP1) and large root pruning (cut off about 1/3 of the root system, RP2) improved WUE and root hydraulic conductivity (Lpr) in the residual root system. At the jointing stage, RP1 and RP2 increased Lpr by 43.9% and 31.5% than the un-cut control under well-watered conditions, and 27.4% and 19.8% under drought stress, respectively. RP1 increased grain yield by 12.9% than the control under well-watered conditions, whereas both pruning treatments had no significant effect on yield under drought stress. The hydroponic experiment demonstrated that root pruning did not reduce leaf water potential but increased residual root hydraulic conductivity by 26.2% 48 hours after root pruning under well-watered conditions. The foregoing responses may be explained by the upregulation of plasma membrane intrinsic protein gene and increases in abscisic acid and jasmonic acid in roots. Increased auxin and salicylic acid contributed to the compensated lateral root growth. In conclusion, root pruning improved WUE in maize by root water uptake.